2019
DOI: 10.1186/s12893-019-0600-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel biodegradable magnesium alloy clips compared with titanium clips for hepatectomy in a rat model

Abstract: Background The use of surgical metal clips is crucial for ligating vessels in various operations. The currently available metal clips have several drawbacks; they are permanent and interfere with imaging techniques such as computed tomography (CT) or magnetic resonance (MR) imaging and carry the potential risk of endo-clip migration. We recently developed a novel magnesium (Mg) alloy for biodegradable clips that reduces artifacts on CT imaging. This study aimed to examine the tolerance, biodegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a maxillofacial/oral environment, the gas development and soft tissue responses including inflammatory and fibroplasia responses could affect both short term and long-term cosmetic appearance of the surgical site of the patient. For instance, it is worth noting that that few studies have shown the potential of using Mg–Zn–Ca alloys as vascular clips [ 106 , 107 ] and these clips are in oral/maxillofacial surgery to get a better access to the surgical site in some cases. Currently, many fixtures used in maxillofacial and mandibular applications uses plates (or miniplates) with a locking screw arrangement that are made from bioinert Ti alloys.…”
Section: Discussionmentioning
confidence: 99%
“…In a maxillofacial/oral environment, the gas development and soft tissue responses including inflammatory and fibroplasia responses could affect both short term and long-term cosmetic appearance of the surgical site of the patient. For instance, it is worth noting that that few studies have shown the potential of using Mg–Zn–Ca alloys as vascular clips [ 106 , 107 ] and these clips are in oral/maxillofacial surgery to get a better access to the surgical site in some cases. Currently, many fixtures used in maxillofacial and mandibular applications uses plates (or miniplates) with a locking screw arrangement that are made from bioinert Ti alloys.…”
Section: Discussionmentioning
confidence: 99%
“…These Mg wires were further processed into hemostatic clips or stents and were widely used in the fields of cardiac surgery [ 276 ] ( Fig. 11 A), general surgery [ [277] , [278] , [279] ] ( Fig. 11 E–G), neurosurgery [ 280 ] ( Fig.…”
Section: Prospects For Biological Matching Spine Fusion Cage Developmentmentioning
confidence: 99%
“…
Fig. 11 A. Mg based coronary artery stent, Zong et al [ 276 ], copyright 2022, ELSVIER, Creative Commons Attribution License; B. Mg wire induced nerve regeneration, Vennemeyer et al [ 280 ], copyright 2015, SAGE; C. Mg wire ligated bladder, Okamura et al [ 281 ], copyright 2021, Springer; D. Mg wire ligated urinary tract, Chang et al [ 282 ], copyright 2020, MDPI, Creative Commons Attribution License; E. Mg wire used for hepatectomy, Urade et al [ 279 ], copyright 2019, BMC, Creative Commons Attribution 4.0 International License; F. Mg wire anastomosed intestine, Zhang et al [ 277 ], copyright 2023, Ke Ai, Creative Commons Attribution License; G. Mg wire used for cholecystectomy, Yoshida et al [ 278 ], copyright, 2017, ELSEVIER; H. Mg wire weaving ACL tendon graft in reconstruction surgery, He et al [ 62 , 91 ], copyright 2022, MDPI, Creative Commons Attribution License and 2024, Ke Ai, Creative Commons Attribution License; I. Mg based scaffold based on Mg wire to treat defect, Xue et al [ 283 ], copyright 2022, IOP, Creative Commons Attribution License.
…”
Section: Prospects For Biological Matching Spine Fusion Cage Developmentmentioning
confidence: 99%